2017
DOI: 10.4238/gmr16029376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity of Leuciscus leuciscus baicalensis using novel microsatellite markers with cross-species transferability

et al.

Abstract: ABSTRACT. We used next-generation sequencing technology to characterize 19 genomic simple sequence repeat (SSR) markers and 11 expressed sequence tag (EST) SSR markers from Leuciscus leuciscus baicalensis, a small freshwater fish that is widely distributed in Xinjiang, China. Primers were used to test for polymorphisms in three L. leuciscus baicalensis populations in Xinjiang. There were 4-27 (average 11.3) alleles (N A ), the expected heterozygosity (H E ) was 0.36-0.94 (average 0.75 ± 0.14), the observed het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Because the whole genome of Meriones meridianus has not been sequenced completely, it is difficult to obtain suitable microsatellite markers by genome sequencing. It has been reported that cross-species amplification of species microsatellite loci in related species is an effective way to isolate microsatellite markers [14,15,22,24]. Since the midday gerbils and Mongolian gerbils are the closely related species, the present study aimed to identify microsatellite loci for Meriones meridianus on the basis of a significant microsatellite marker system (28 loci markers) using the method of cross-amplification of species, which has already been established for the Mongolian gerbil [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because the whole genome of Meriones meridianus has not been sequenced completely, it is difficult to obtain suitable microsatellite markers by genome sequencing. It has been reported that cross-species amplification of species microsatellite loci in related species is an effective way to isolate microsatellite markers [14,15,22,24]. Since the midday gerbils and Mongolian gerbils are the closely related species, the present study aimed to identify microsatellite loci for Meriones meridianus on the basis of a significant microsatellite marker system (28 loci markers) using the method of cross-amplification of species, which has already been established for the Mongolian gerbil [8].…”
Section: Introductionmentioning
confidence: 99%